A conceptual framework for the adoption of Islamic banking in a pluralistic-secular nation: Nigerian perspective. Issue 4 (12th November 2018) - Ezeh, Precious Chikezie; Nkamnebe, Anayo D.
Abstract : Purpose: Islamic banking is an emerging product in Nigeria; it has evolved as a new reality in the Nigerian financial scene since 2011. Thus, the purpose of this paper is to propose a conceptual framework for the study of Islamic banking adoption behavior among bank customers in Nigeria. Design/methodology/approach: This study is a literature and theoretical review of past studies to develop a comprehensive framework for the study of Islamic banking adoption behavior in Nigeria. Findings: In this conceptual study, the researcher identified 12 independent variables, namely, relative advantage, compatibility, complexity, observability, trialability, uncertainty, promotional efforts, awareness, customer involvement, perceived information quality, profit/loss sharing and religiosity, as suitable variables for the study of Islamic bank adoption in Nigeria. Practical implications: As Islamic banking is an innovative and unique product, which differs from conventional banking, it is hopeful that upon validating the framework, it will provide useful insight on the adoption behavior of Islamic bank customers in Nigeria. Social implications: This study will be useful to Islamic banks in gaining and maintaining their existing customer, and policymakers, regulators and other relevant stakeholders will be able to strategize in accordance with their respective assignments toward the development and growth of the Nigerian financial industry. Originality/Value: Most previous studies concentrated on product attributes of innovation adoption. But, this current study inculcated the consumers' attitude and perception toward adoption of Islamic banking. Thus, the authors then propose several factors that can influence adoption of Islamic banking in Nigeria.